Sur la stratification des congruences de droites à l’aide des surfaces développables - Vaškas, P. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: П. Вашкас. О расслоении конгруэнций прямых при помощи некоторых развертывающихся поверхностей P. Vaškas. Apie tiesių kongruencijų išsluoksniavimą išklojamųjų paviršių pagalba